Experimental study on revetec engine cam performance - Maisara Mohyeldin, Gasim Mohamed; Lee, Giok Chui; Khirul Azhar, Anwar (IOP Publishing, 2012)
In Revetec engine (three-lobed) cam replaces the crankshaft to convert the reciprocating motion of the engine piston, to a rotating motion in the drive line. Since the cam controls the piston movement, the cam profile has a great effect on engine performance. In this paper an experimental study was done to a (three- lobed) cam with Cycloidal motion profile but with different ratios between the base circle radius of the cam and the radius of the roller follower. DEWESoft was used to find the displacement and the vibration of the piston, and compare the actual results from the test with the theoretical results from the cam profile equation. The results showed that there is a periods of miss contact between the follower and the cam when the ratio between the base circle radius of the cam and the radius of the roller follower is less than a certain value, and also increasing of vibration. The suggested ratio between the cam and follower radius is to be more than 2:1.